Trastorno mental y del comportamiento en paciente multípara de 22 años de edad. - León Bea, Eusebia Natali (2022)
Postpartum depression during the first days is more easily identified and is of the utmost importance since the events that harm the mother help us to look for more alternatives to identify any pathology in accordance with the symptoms and signs that the patient presents. and thus reduce maternal and neonatal complications. Although its onset is not fully defined, it can be mentioned that postpartum depression triggers some of the biological, psychological and social factors that can affect the postpartum mother. The case of a 22-year-old patient is presented, she comes for presenting a clinical picture characterized by pain in the lumbosacral region, with a gestation that corresponds to 37 weeks that ends in cephalo-vaginal delivery and that a few hours after delivery presents signs and symptoms. of psychopsychiatric mental disorder.